ANDROID-BASED MOBILE LEARNING MEDIA WITH CHARACTER - Ahmad Yani; Anggi Pramita; Hartono Hartono; Hodiyanto Hodiyanto (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
This study aims to produce a android-based mobile learning media with character. The research method is a research and development method with a 4D design which is limited to Define, Design, and Develop. The subjects in this study were students of class VIII of Public Junior High School 10 Sungai Kakap as many as 14 students. The instruments were validation sheets, questionnaires of teacher and student and posttest questions. Learning media is said to be valid, practical and effective if the percentage is above 60%. Based on the results of the research, it is found that the android-based mobile learning media is valid, practical and effective. The validation of it has a validity level of 90.53% with very valid criteria, while the practicality level of learning media is 90.16%. with very practical criteria, and the effectiveness of learning media is 85.71% with very effective criteria.